2014
DOI: 10.1111/aogs.12490
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of bowel endometriosis: resection margins as a predictor of recurrence

Abstract: Positive bowel resection margins as well as age <31 years and body mass index ≥23 kg/m(2) appear to be independent predictors of disease recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 18 publications
1
14
0
2
Order By: Relevance
“…The standardized laparoscopic surgical technique for DIE performed in our clinic has been described previously [24]. SUP was treated by excision via monopolar needle or scissors.…”
Section: Surgical Techniquementioning
confidence: 99%
“…The standardized laparoscopic surgical technique for DIE performed in our clinic has been described previously [24]. SUP was treated by excision via monopolar needle or scissors.…”
Section: Surgical Techniquementioning
confidence: 99%
“…As far back as 1990, surgeons have suggested that excision of macroscopic endometriosis lesions might leave behind microscopic implants (4,5). Other authors have focused their studies on bowel endometriosis and attempted estimating the risk of residual microscopic implants on the bowel after disc excision (6) or colorectal resection (7)(8)(9)(10). It is unclear whether such residual microimplants or bowel occult microscopic endometriosis (BOME) contribute to postoperative symptoms or recurrences of macronodules, because studies remain vague concerning the degree of risk of such outcomes (10).…”
mentioning
confidence: 99%
“…Recurrence rate for shaving was reported at 22.2%, for discoid resection 5.17%, and in segmental resection 2.19%; these rates were significantly different [37]. Positive bowel resection margins as well as age <31 years and body mass index ≥23kg/m2 appear to be important independent predictors of disease recurrence [40].…”
Section: /6mentioning
confidence: 90%